Gasdermins assemble; recent developments in bacteriology and pharmacology - Greenwood, Claudine S.; Wynosky-Dolfi, Meghan A.; Beal, Allison M.; Booty, Lee M. (Frontiers in Immunology, 2023)
The discovery of gasdermin D (GSDMD) as the terminal executioner of pyroptosis provided a large piece of the cell death puzzle, whilst simultaneously and firmly putting the gasdermin family into the limelight. In its purest form, GSDMD provides a connection between the innate alarm systems to an explosive, inflammatory form of cell death to jolt the local environment into immunological action. However, the gasdermin field has moved rapidly and significantly since the original seminal work and novel functions and mechanisms have been recently uncovered, particularly in response to infection. Gasdermins regulate and are regulated by mechanisms such as autophagy, metabolism and NETosis in fighting pathogen and protecting host. Importantly, activators and interactors of the other gasdermins, not just GSDMD, have been recently elucidated and have opened new avenues for gasdermin-based discovery. Key to this is the development of potent and specific tool molecules, so far a challenge for the field. Here we will cover some of these recently discovered areas in relation to bacterial infection before providing an overview of the pharmacological landscape and the challenges associated with targeting gasdermins.